IL-6 Inhibition Reduces STAT3 Activation and Enhances the Antitumor Effect of Carboplatin - Zhi-Yong Wang; Jun-Ai Zhang; Xian-Jin Wu; Yan-Fang Liang; Yuan-Bin Lu; Yu-Chi Gao; You-Chao Dai; Shi-Yan Yu; Yan Jia; Xiao-Xia Fu; Xiaoquan Rao; Jun-Fa Xu; et al. (Mediators of Inflammation)
Recent studies suggest that tumor-associated macrophage-produced IL-6 is an important mediator within the tumor microenvironment that promotes tumor growth. The activation of IL-6/STAT3 axis has been associated with chemoresistance and poor prognosis of a variety of cancers including colorectal carcinoma and thus serves as a potential immunotherapeutic target for cancer treatment. However, it is not fully understood whether anticytokine therapy could reverse chemosensitivity and enhance the suppressive effect of chemotherapy on tumor growth. In this study, we aimed to investigate the effect of IL-6 inhibition therapy on the antitumor effect of carboplatin. Enhanced expression of IL-6 and activation of STAT3 were observed in human colorectal carcinoma samples compared to normal colorectal tissue, with higher levels of IL-6/STAT3 in low grade carcinomas. Treatment of carboplatin (CBP) dose-dependently increased IL-6 production and STAT3 activation in human colorectal LoVo cells. Blockade of IL-6 with neutralizing antibody enhanced chemosensitivity of LoVo cells to carboplatin as evidenced by increased cell apoptosis. IL-6 blockade abolished carboplatin-induced STAT3 activation. IL-6 blockade and carboplatin synergistically reduced cyclin D1 expression and enhanced caspase-3 activity in LoVo cells. Our results suggest that inhibition of IL-6 may enhance chemosensitivity of colon cancers with overactive STAT3 to platinum agents.